Analysis of e-commerce repurchase intention by consumers during the COVID-19 pandemic based on social network behavior - Mendoza Fernández, Grecia Ximena (2024)
The emergence of global social isolation in the context of the Covid-19 pandemic accelerated the growth of ecommerce to a high level, that allowed companies to become more technologically aware of customer management, moving from a traditional system to a modern one. However, this change has not been carried out in a drastic way, and even not completely, because the Peruvian commercial environment is difficult to penetrate, and it is complicated to displace the already established sales channels. Therefore, in this research, data was collected from the main ecommerce companies in the Peruvian market, at the national level (Falabella Peru and Ripley Peru), to demonstrate the importance of social media management as a factor promoting repurchase intention and that, consequently, it is an important aspect to consider during the elaboration of loyalty models in organizations. For this reason, a survey was used as a data collection tool and the information obtained was analyzed using Structural Equation Modeling with IBM SPSS AMOS software. Given this, the most relevant result obtained was that social media activities have a positive and significant effect on repurchase intention. On the contrary, brand equity and customer relationship have a positive relationship, but not as relevant for repurchase intention.